Vaccine communication and the media credibility in addressing vaccine hesitancy: a focus on Malaysia - Wan Mohd Ghazali, Wan Norshira; Wok, Saodah; Mohamed, Shafizan; Yusoh, Mohd Helmi (Intech Open, 2022)
The resurgence of vaccine-preventable diseases such as polio, diphtheria, measles and the like shows that the anti-vaccine movement is gaining popularity and effectiveness in bolstering its views. Multiple studies have shown worrying trends of distrust towards vaccines, medical professionals, vaccine scientists and the government agencies that promote vaccination. It is observed that the current anti-vaccine discourses and misinformation about vaccines on social media are fuelling fear of vaccination among the public. To minimise the spread of vaccine-preventable diseases, the media has considerable potential to influence the public’s understanding of how vaccines function. Therefore, this chapter proposed the adoption of a media guide to assist media practitioners in reporting vaccination stories. It will highlight an influential role that the media can play by enlisting the assistance of experts and health professionals to dispel erroneous beliefs about vaccinations and aggressively promote vaccination among influential persons and the general public. This chapter argued that responsible and ethical reporting will aid in raising awareness of the public health implications of the anti-vaccine sentiment, thereby combating the transmission of messages that drive vaccine fear and rejection. The chapter also addressed how insights provided by Ihlen on rhetorical communication can enhance the effectiveness of delivering vaccine-related messages.